Risk factors for cerebrovascular disease, Babol, 2000-02 - A Ahmadi Ahangar (Babol University of Medical Sciences, 2005)
Background and objective: Cerebrovascular disease (CVD) or stroke is the third cause of mortality and morbidity after CHD and cancer. Incidence of stroke has been decreasing because of identification and prevention of its risk factors. It is important to know the distribution of its risk factors because most of them are preventable and curable. Methods: This study was performed on 250 patients with diagnosis of CVD by neurologists and were hospitalized in Babol Yahyanejad hospital from autumn 2000-02. The type of stroke was defined by brain CT scan. The information including age, gender, blood pressure, blood sugar and cholesterol, history of IHD or CVD and smoking were gathered from the files and analyzed by Chi-square test and (P<0.05) was considered significant. Findings: Stroke happened more in people aged 65 to 74 years (42.4%) and in women (52%). Hypertension as the most common risk factor significantly differed from the others (P=0.000). The second and third risk factors were IHD and diabetes, respectively. Also the hemorrhagic type was significantly higher than ischemic type and lead to more death cases. Conclusion: It is recommended to do a screening program for detection and treatment of asymptomatic hypertension and also further studies on high prevalence of stroke in women and determining the cause of IHD being the second risk factor rather than diabetes in this region.